(3GdCNHGQ hGdBKGQs ((3Ydi Hf eMeO GdZhQj GdbdYj GdTGaYj s)
(3ChdgG (B:s
(3hHYO aEfi C MHHJ Cf CLeY CNHGQ COGhi HgG bShI bdHj hCSJLdH HgG OehY Yjfi s
(3BNQgG (B:s
(3hdGJNa ai Gddg ef habc Gddg deG JTJgj s
(3hgh cJGH aj CNHGQ GdCfHjGA hCNHGQ fHjfG eMeO Ydjg GdUdGI hGdSdGes
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B21 s
Keywords: (3GdJGQjNs